Antipsychotic Treatment of 22q11.2 Deletion Syndrome-Related Psychoses - Angelopoulos, Elias; Theleritis, Christos; Economou, Marina; Georgatou, Korina; Papageorgiou, Charalambos C.; Tsaltas, Eleftheria (Pharmacopsychiatry, 2017)
In the recent study by Verhoeven and Egger, 2015 and the recent letter to the editor by Boot et al. 2015 an emphasis is given to the best possible pharmacological treatment of 22q11-2 Deletion-Syndrome related psychoses. We would like to present the case of a 23-year old Cypriot patient with 22q11.2 deletion syndrome who fulfilled criteria for treatment resistant schizophrenia (TRS). He was sequentially treated with aripiprazole, risperidone, olanzapine, haloperidol and a combination treatment with olanzapine and haloperidol. Clozapine was the only antipsychotic medication that has improved his condition.